Isolation and Characterization of Both Human and Mouse Tfh/Tfr Cells. Issue 11 (8th November 2021) - Tulyeu, Janyerkye; Søndergaard, Jonas N.; Sakaguchi, Shimon; Wing, James B.
Abstract: Regulatory T cells (Tregs) expressing the transcription factor Foxp3 have a critical role for the control of immune homeostasis. The Treg subgroup T follicular regulatory cells (Tfr) have a specialized function to travel to the B cell follicle and control antibody responses. While Tfr may be identified by their protein or gene expression profiles, the use of in vitro functional assays to determine their suppressive capacity is important to further characterize these cells. Here we present methods for the identification and purification of Tfr from both mice and humans followed by co‐culture with B cells and T follicular helper cells (Tfh). The suppressive activity of the Tfr is then assessed by the ability to prevent Tfh‐dependent B cell class switching and plasma blast formation measured by flow cytometry and immunoglobulin production in culture supernatants measured by enzyme‐linked immunosorbent assay. These assays will also provide in‐depth characterization of the functional suppressive capacity of any isolated Tfr or Treg population. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Isolation of murine T follicular regulatory cells Basic Protocol 2 : Measurement of murine T follicular regulatory cell suppressive function Basic Protocol 3 : Isolation of human T follicular regulatory cells Basic Protocol 4 : Measurement of human T follicular regulatory cell suppressive function